Perceptual training modifies temporal sensitivity and a sense of agency - Venskus, Agnese; Gooding, Peter L. T.; Hughes, Gethin (Frontiers in Psychology, 2023)
Perceptual training has been argued to be a potential means to modify temporal sensitivity (the ability to detect time-based discrepancy between two stimuli) with previous studies providing preliminary evidence that perceptual training can lead to an increased temporal sensitivity. However, previous studies have not employed a control group, and therefore cannot rule out the possibility that the observed effects are due to repeated completion of the task, rather than the training itself. Moreover, despite temporal sensitivity being suggested to be an important aspect of sense of agency, the effects of perceptual training on sense of agency have not been explored. Therefore, the aim of this study was to explore the effects of perceptual training on sense of agency as well as replicate previously observed effects on temporal sensitivity while utilising a more rigorous methodology. Given the existing literature, it was predicted that sense of agency, and temporal sensitivity, will be enhanced following perceptual training. Temporal sensitivity was only weakly modified by perceptual training, when compared to the control condition. Sense of agency was significant modulated by perceptual training, over and above the control condition. The findings present novel evidence indicating that perceptual training can influence high level processes such as sense of agency, as well as temporal sensitivity.